2020
DOI: 10.1186/s40001-020-00453-y
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-like cells change gene expression of bone remodelling markers in transwell cultures

Abstract: Introduction Periprosthetic fibroblast-like cells (PPFs) play an important role in aseptic loosening of arthroplasties. Various studies have examined PPF behavior in monolayer culture systems. However, the periprosthetic tissue is a three-dimensional (3D) mesh, which allows the cells to interact in a multidirectional way. The expression of bone remodeling markers of fibroblast-like cells in a multilayer environment changes significantly versus monolayer cultures without the addition of particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Detailed histomorphological characteristics were not performed in the current study due to a limited number of cells per donor. Hartmann et al found conglomerates of PPFs in frozen sections of transwell cultures forming a polylayer structure (34). This coincides with findings of Sabater et al (27), showing that cultivating fibroblasts in transwell systems lead to an increased number of cells and higher cell mass compared to cultures on standard well bottoms, despite the smaller surface of the transwell membranes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Detailed histomorphological characteristics were not performed in the current study due to a limited number of cells per donor. Hartmann et al found conglomerates of PPFs in frozen sections of transwell cultures forming a polylayer structure (34). This coincides with findings of Sabater et al (27), showing that cultivating fibroblasts in transwell systems lead to an increased number of cells and higher cell mass compared to cultures on standard well bottoms, despite the smaller surface of the transwell membranes.…”
Section: Discussionsupporting
confidence: 62%
“…Morphological characterization of PPFs in transwell cultures had been performed by our group (34). Detailed histomorphological characteristics were not performed in the current study due to a limited number of cells per donor.…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 is a paracrine factor released from mesenchymal stem cells with powerful immunomodulatory functions and upregulates IL-10 secreted by macrophages and stimulates M2 macrophage polarization to accelerate the recovery of damaged tissues [ 44 ]. However, PGE2 also promotes RANKL expression in periprosthetic fibroblasts [ 45 ].…”
Section: Exosomes and Macrophage Polarizationmentioning
confidence: 99%
“…Several studies demonstrated that many MMPs might lead to prosthetic loosening and osteolysis through pathological extracellular matrix degradation and periprosthetic connective tissue/bone remodeling [ 89 92 ]. Periprosthetic fibroblast-like cells express MMP-13 in response to induction of wear particles, and the increase in matrix metalloproteinases destroys the periprosthetic tissue [ 45 ]. Blocking TNF- α and IL-1 β receptors does not attenuate the damaging effects of exosomes on the extracellular matrix, suggesting that the mechanism of increased matrix metalloproteinase production caused by exosomes is independent of the TNF- α -induced inflammatory response.…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%